2020
DOI: 10.20944/preprints202010.0548.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Accessibility Benefits of Opening Gated Communities in China: A Case Study of Shanghai

Abstract: Opening gated-communities (GCs) has been widely discussed for urban inclusion and revitalization. With the policies of opening GCs being promoted in China, quantitative and comprehensive evaluation of the potential benefits is heavily needed. Taking Shanghai as an example, this study quantifies and analyzes the accessibility benefits and risks of opening GCs with factors including GC types, opening levels, travel modes, and travel destinations considered. We found that (1) opening GCs can bring 50m+ accessibil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Walking distance is an essential factor influencing whether or not people choose public transport, especially in areas of large residential sites and non-central suburbs [ 1 , 2 ]. Some studies found that it has the highest proportion among the factors influencing transit ridership [ 3 ]. In this sense, the characteristics of a built environment that increase the distances in walking routes to public transit should be well examined to make better policies.…”
Section: Introductionmentioning
confidence: 99%
“…Walking distance is an essential factor influencing whether or not people choose public transport, especially in areas of large residential sites and non-central suburbs [ 1 , 2 ]. Some studies found that it has the highest proportion among the factors influencing transit ridership [ 3 ]. In this sense, the characteristics of a built environment that increase the distances in walking routes to public transit should be well examined to make better policies.…”
Section: Introductionmentioning
confidence: 99%